2020
DOI: 10.2174/1389557520666200313120419
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Current Pharmacological Perspectives of Sesamol: A Review

Abstract: Sesame (Sesamum indicum L.) seeds have been authenticated for its medicinal value in both Chinese and Indian systems of medicine. Its numerous potential nutritional benefits are attributed to its main bioactive constituents, sesamol. As a result of those studies, several molecular mechanisms are emerging describing the pleiotropic biological effects of sesamol. This review summarized the most interesting in vitro and in vivo studies on the biological effects of sesamol. The present work summarises data availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…The LDH inhibitors reported till date and explored herein (Tables 2 and 3; structures of inhibitors are detailed in Item 4, SI) are compounds that have antioxidant properties. For example, sesamol (a phenol derivative obtained from sesame seeds) is known to have antioxidant and pleiotropic biological effects (Bosebabu et al, 2020). Sesamol inhibits LDH reactions even though it does not have a low K d value for the protein.…”
Section: Resultsmentioning
confidence: 99%
“…The LDH inhibitors reported till date and explored herein (Tables 2 and 3; structures of inhibitors are detailed in Item 4, SI) are compounds that have antioxidant properties. For example, sesamol (a phenol derivative obtained from sesame seeds) is known to have antioxidant and pleiotropic biological effects (Bosebabu et al, 2020). Sesamol inhibits LDH reactions even though it does not have a low K d value for the protein.…”
Section: Resultsmentioning
confidence: 99%
“…19 Sesamol could provoke its antiinflammatory effect by down-regulating transcription of the promoting inflammatory markers such as cytokines, redox status, protein kinases, and enzymes. 20…”
Section: Sesamol Decreased the Al 2 O 3 -Nps-induced Elevation Of Hep...mentioning
confidence: 99%
“…14 It possesses cardiac, neural, and hepatorenal protective effects, [15][16][17][18] in addition to its hypolipidemic, anti-hypertensive, anti-aging, anti-oxidative, anti-inflammatory, anti-apoptotic, anti-mutagenic, and anticancer properties. 15,19,20 Liver and kidneys are among the main target organs for Al 2 O 3 -NPs accumulation. 21 Therefore, the current study aimed to investigate the hepatorenal adverse effects induced by aluminum-oxide nanoparticles in rats, focusing on the mechanistic roles of oxidative damages, inflammation, and apoptosis; and to evaluate the prospective efficacy of sesamol.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sesamol as an oxidative stress scavenger may suppress apoptosis and increase follicular quality because the accumulation of oxidative stress in follicles leads to a decrease in the quality of follicles 40–42 . Also, the protective effect of sesamol may be achieved by restoring the activity of endogenous antioxidants 22,43 . Ren et al have reported that antioxidative and protective effects of sesamol take place by regulating the Nrf2/Keap1 pathway which is a key pathway for antioxidants to eliminate ROS and protect cells from oxidative stress and apoptosis 44 .…”
Section: Discussionmentioning
confidence: 99%